2017
DOI: 10.3390/pathogens6040061
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Enzootic Equine Influenza Virus among Horses in Mongolia

Abstract: Horses are critically important for Mongolian herders’ livelihoods, providing transportation and food products, and playing important cultural roles. Equine influenza virus (EIV) epizootics have been frequent among Mongolia’s horses, with five occurring since 1970. We sought to estimate the prevalence for EIV infection among horses and Bactrian camels with influenza-like illness between national epizootics. In 2016–2017, active surveillance for EIV was periodically performed in four aimags (provinces). Nasal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Since 1974 there have been five EIV epizootics documented in Mongolia: 1974–1975, 1983–1984, 1993–1994, 2007–2008, and 2011 [28]. As vaccination coverage in the country is seemingly very low [42], it can be reasonably assumed that most seropositive horses have acquired EIV immunity by natural infection, which is known to induce a potent immunological response. Since all AIVs studied here possess the same subtype as EIV (H3), the high seroprevalence of the latter could provide enough pre-existing immunity against H3 AIVs, thus acting as an effective barrier against AIV emergence in horses.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1974 there have been five EIV epizootics documented in Mongolia: 1974–1975, 1983–1984, 1993–1994, 2007–2008, and 2011 [28]. As vaccination coverage in the country is seemingly very low [42], it can be reasonably assumed that most seropositive horses have acquired EIV immunity by natural infection, which is known to induce a potent immunological response. Since all AIVs studied here possess the same subtype as EIV (H3), the high seroprevalence of the latter could provide enough pre-existing immunity against H3 AIVs, thus acting as an effective barrier against AIV emergence in horses.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, EIV was also reported in India (2008 and2009) and Mongolia (2008Mongolia ( , 2012Mongolia ( , and 2016. Phylogenetic analyses showed that all Indian and Mongolian strains were similar to the FC2 viruses circulating in China between 2007 and 2008 (9,(15)(16)(17). Finally, EIV was also detected in Kazakhstan during 2007 and 2012, and the isolates were closely related to Mongolian and Chinese FC2 strains (18).…”
mentioning
confidence: 88%
“…Similarly, there was no positive case observed out of 131 camels tested. This study reported a sporadic incidence of enzootic EIV in Mongolia (Sack et al, 2017 ).…”
Section: Epidemiology and Evolutionmentioning
confidence: 92%